EEG alpha-activity in neurotherapy of attention deficit syndrome using game biofeedback - I. A. Stoller; M. V. Sukholentseva; N. N. Tkachenko; Ye. G. Veryovkin; M. B. Shtark; S. V. Yarosh (Бюллетень сибирской медицины, 2010)
The dynamics of the segment characteristics of alpha-rhythm and their correlation with the «behaviour» of dipole sources of alpha-band in relation to beta-stimulating neurofeedback in schoolchildren with ADHD syndrome were analyzed. Effective training results in forming of neuronal groups in alpha-band which correlate to the new dipole sources. Possible place of alpha-generating system in the mechanisms of effective neurobiofeedback is discussed.